Defining the impact of Peyronie's disease on the psychosocial status of gay men. (10th October 2020) - Salter, Carolyn A.; Nascimento, Bruno; Terrier, Jean‐Etienne; Taniguchi, Hisanori; Bernie, Helen; Miranda, Eduardo; Jenkins, Lawrence; Schofield, Elizabeth; Mulhall, John P.
Abstract: Background: Little sexual health research has been conducted in gay men. Anecdotally, this population seems to experience more bother related to Peyronie's disease (PD). Objectives: To examine the impact of PD on psychosocial factors in gay vs straight men. Materials and Methods: All PD patients who were seen in the sexual medicine clinic were included. They completed three instruments: the PD questionnaire (PDQ), Self‐Esteem and Relationship (SEAR) questionnaire, and a depression questionnaire (CES‐D). We described demographics and sexual variables by sexual orientation. We then compared PDQ items and summary scores by sexual orientation, using a series of independent samples t tests. Results: 34 consecutive gay and 464 straight men were included. Age and baseline characteristics were similar between the two cohorts, with the exception that fewer gay men were partnered (56% vs 87%, P < .01), and those with a partner had a shorter relationship duration: 109 ± 9 months vs 262 ± 175 months, P < .01. For the SEAR questionnaire, gay men demonstrated a more significant psychosocial impact of PD overall with lower SEAR sums (41 vs 57, P = .01) and a lower sexual relationship subdomain score (28 vs 47, P < .01). 41% of gay men vs 26% of straight men had CES‐D scores consistent with depression as defined by a score of ≥16 ( P = .09). In the PDQ domains, gay men scored less favorably with regard to bother scores (7 vs 5, P = .03) and pain scores (8 vs 4, P = .04). Discussion: Gay men with PD experience significantly more psychosocial impact as evidenced by less favorable SEAR sum and sexual relationship scores, CES‐D scores, and PDQ pain and bother domain scores. Conclusion: The psychosocial impact of PD is significant in all men, but it appears to be greater in gay men.